Kartu interaktif QR code: Media kolaboratif pembelajaran PAI - Athallah, Muhammad Farhan (Maliki Interdisciplinary Journal, 2025)
Islamic Religious Education (IRE) faces challenges in delivering moral and spiritual content in ways that are engaging and relevant to students. This article examines the application of an innovative learning medium called Interactive Cards as a solution to enhance the appeal and effectiveness of IRE instruction. Using a qualitative descriptive approach, this study explores the concept, implementation, and potential benefits of Interactive Cards in the learning process. This medium integrates physical cards with QR code technology linked to instructional videos, combined with group discussions and presentations. The findings indicate that Interactive Cards can increase student active participation, strengthen the understanding of moral values, and develop 21st-century skills such as critical thinking, communication, and collaboration. Therefore, Interactive Cards represent a promising innovation for creating dynamic, interactive, and contextual IRE learning experiences.